An Evaluation of the Principles of Faith Expressed in the Poems of Shah Ismail Khatai - Keleş, Bülent (Journal of Alevism-Bektashism Studies, 2024)
Shah Ismail is a highly debated figure, both for his historical personality and religious affiliation, especially in the context of Ottoman-Safavid relations and the fact that a large portion of his followers were Ottoman subjects. Among the issues placed at the center of the debate by his adversaries are accusations that he disregarded fundamental principles of Islam, such as the abolition of Islamic law (Sharia) as established by the Ahl al-Sunnah, undermining the religious authority of Prophet Muhammad, and nullifying the teachings of the Qur’an, which are considered core beliefs of Islam. The Ottoman scholars of his time, who saw him as an enemy and marginalized him, claimed that he led the Turkmen in Anatolia astray, making them his followers and turning them to Shia Islam. Additionally, it is claimed that Shah Ismail, the seventh leader of the Safavi Sufi order, transformed the originally Sunni Safavi order into a structure that promoted Shia missionary activities. Shah Ismail, who Sunni scholars accused of being a Shia, was not accepted by Shia Muslims either. Even modern Shia writers, like Ali Shariati, accuse him and the Safavid State he established of distorting Shia Islam and deviating from the true Shia faith centered around Ali.In the eyes of his followers, however, he occupies a completely different position. It can even be said that all the attributes such as heroism, wisdom, courage, and charity, which Alevi people associate with Ali, have been embodied in Shah Ismail. For Alevis, he is not only the perfect human (İnsan-i Kâmil) and a spiritual guide but also one of the pioneers who carried their belief to future generations. He is a revered figure whose sayings are recited in almost every Alevi cem ritual. Therefore, understanding his beliefs is a crucial aspect. The claims made by his adversaries about him attempting to undermine the core principles of Islam and abolish Prophet Muhammad’s Sharia can be understood as politically motivated. Investigating his belief system is necessary to comprehend the nature of these accusations. In this study, the belief principles reflected in his poetry are analyzed using document analysis, a qualitative research method from the social sciences. By examining the belief principles emphasized in his divan, which has been Latinized by various researchers, and analyzing documents such as books, articles, and archival records through content analysis, this study explores whether the allegations made against Shah Ismail hold any truth. The study also highlights the alignment or contradictions between the belief principles he emphasized in his poetry and the Shia and Sunni Islamic traditions.
Keywords: Shah Ismail; Alevism; Faith; Admission; Belief Principles